Critical Thinking Skills of Physics Teachers for Inquiry Based Learning Practices - Bako , Aliyu; Aliah Phang, Fatin (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at investigating the critical thinking skills of physics teachers in inquiry-based classrooms. The development of critical thinking became inherent in education because it is a tool for attaining intellectual discipline, integrity, freedom, citizenship, creativity, and empathy in every society. Descriptive analysis was used on the Lawson classroom reasoning test administered to a sample of 90 IBL physics teachers in Kebbi state secondary schools; the overall mean score value was calculated to be 26.83 out of a 120 obtainable score. The result indicated a weak level of critical thinking skills of the teachers. Further analysis shows that the teachers are weak in hypo-deductive reasoning, deductive reasoning control, and combinational reasoning skills. Teachers with low critical thinking may find inquiry-based classrooms monotonous. Therefore, to improve the practice of IBL among the physics teachers, their critical thinking skill needs to be strengthened, especially in making hypodeductive reasoning, deductive reasoning control, and combinational reasoning skills.